2017
DOI: 10.1186/s12864-017-3846-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metabolome and transcriptome analysis of Magnolia champaca identifies biosynthetic pathways for floral volatile organic compounds

Abstract: Background Magnolia champaca, commonly known as champak is a well-known tree due to its highly fragrant flowers. Champak floral scent is attributed to a complex mix of volatile organic compounds (VOCs). These aromatic flowers are widely used in flavors and fragrances industry. Despite its commercial importance, the VOC biosynthesis pathways in these flowers are largely unknown. Here, we combine metabolite and RNA sequencing (RNA-seq) analyses of fully opened champak flowers to discover the active VOC biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…The proteins they encode are 554 (CfTPS1), 586 (CfTPS2), and 591 (CfTPS3) amino acids in length. A sequence alignment revealed that all of the CfTPS proteins contained the conserved 'DD XX D' and 'NSE/DTE' motifs that are essential for the binding of the co-factors Mg 2+ or Mn 2+ to catalyze terpene biosynthesis [19].…”
Section: Identification Of Cftps Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…The proteins they encode are 554 (CfTPS1), 586 (CfTPS2), and 591 (CfTPS3) amino acids in length. A sequence alignment revealed that all of the CfTPS proteins contained the conserved 'DD XX D' and 'NSE/DTE' motifs that are essential for the binding of the co-factors Mg 2+ or Mn 2+ to catalyze terpene biosynthesis [19].…”
Section: Identification Of Cftps Genesmentioning
confidence: 99%
“…The general biochemical pathways leading to the different classes of volatiles are relatively well understood, and several key protein families such as the terpene synthase (TPS) family, BAHD acyltransferase family, and small molecule methyltransferase families have been described to play important roles in the formation of floral volatiles [14][15][16][17]. In many of these studies, the successful identification of scent-producing genes was based on the integration of metabolomic and transcriptomic data [18][19][20]. TPSs involved in the biosynthesis of floral volatile terpenes, particularly monoterpenes (C 10 ) and sesquiterpenes (C 15 ), belong to TPS-a, TPS-b, and TPS-g subfamilies [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the direct economic benefits provided by tree species, i.e., timber and non-timber products, gaming and tourism, forests have an immensurable ecological value, being the major determinants for water, oxygen, carbon, and energy balance and can be seen as a major opportunity to mitigate climate change effects [12], i.e., continued drought, increased soil and water salinization and acidification, and intensification of extreme temperatures [13]. In forest tree metabolomics research, most biological questions are indeed related to the responses towards the acclimation and adaptation to a permanently changing environment [14][15][16][17][18][19][20][21][22][23][24][25][26] as well as to the identification of potentially active components in tree species of pharmacological, agricultural, environmental, or industrial importance [27][28][29][30][31][32][33].…”
Section: Biological Question Formulationmentioning
confidence: 99%
“…However, the genetic improvement of floral scent falls behind breeding research aimed at improving flower shapes and colors (Dudareva and Pichersky ). Nonetheless, because of increasing consumer demand, more studies are beginning to focus on scent traits (Jin et al , Yue et al , Dhandapani et al , Hu et al , Zhao et al ).…”
Section: Introductionmentioning
confidence: 99%